Government Liability Towards the Amount of Savings by Public Housing Savings Participants - Riqiey, Baharuddin (Alauddin Law Development Journal, 2025)
Article 28H Paragraph (1) of the Indonesian constitution expresses that the government is responsible for the availability of housing. In line with that, the government launched solution by holding the People's Housing Savings (Tapera). This study aims to examine and analyze the appropriateness of the amount of Tapera participant savings reviewed from the perspective of good governance and the mechanism for suing the government. The method used is the legislative and conceptual approach. The results of this study indicate that the amount of Tapera participant savings in Article 15 of Government Regulation No. 21 of 2024 is not by the principles of good governance. This is because the high amount of participant savings is considered to burden the lower class, lose the opportunity to participate in the Tapera program, and favor the middle to upper class. Therefore, the community can sue the government through the civil law or Ombudsman.